The interplay of maternal and offspring obesogenic diets: the impact on offspring metabolism and muscle mitochondria in an outbred mouse model - Xhonneux, Inne; Marei, Waleed F. A.; Meulders, Ben; Andries, Silke; Leroy, Jo L. M. R. (Frontiers in Physiology, 2024)
Consumption of obesogenic (OB) diets increases the prevalence of maternal obesity worldwide, causing major psychological and social burdens in women. Obesity impacts not only the mother's health and fertility, but also elevates the risk of obesity and metabolic disorders in offspring. Family lifestyle is mostly persistent through generations, possibly contributing to the growing prevalence of obesity. We hypothesized that offspring metabolic health is dependent both on maternal and offspring diet and their interaction. We also hypothesised that the sensitivity of the offspring to the diet may be influenced by the match or mismatch between offspring and maternal diets. To test these hypotheses, outbred Swiss mice were fed a control (C, 10% fat, 7% sugar, n=14) or OB diet (60% fat, 20% sugar, n=15) for 7 weeks, then mated with same control males. Mice were maintained on the same corresponding diet during pregnancy and lactation, and the offspring were kept with their mothers until weaning.The study focused only on female offspring, which were equally distributed at weaning and fed C or OB diets for 7 weeks, resulting in 4 treatment groups: C-born offspring fed C or OB diets (C»C, C»OB) and OB-born offspring fed C or OB diets (OB»C, OB»OB). Adult offspring systemic blood profile (lipid and glucose metabolism) and muscle mitochondrial features were assessed. We confirmed that offspring OB diet majorly impacted offspring's health by impairing offspring's serum glucose and lipid profiles, associated with abnormal muscle mitochondrial ultrastructure. Contrarily, maternal OB diet was associated with increased expression of mitochondrial complex markers and mitochondrial morphology in offspring muscle, but no additive effects of (increased sensitivity to) an offspring OB diet were observed in pups born to obese mothers. In contrast, their metabolic profile appeared to be healthier than those born to lean mothers and fed an OB diet. These results are in line with the Thrifty Phenotype Hypothesis, suggesting that OB-born offspring are better adapted towards an environment with a high energy availability later in life. Thus, using a murine outbred model, we could not confirm that maternal obesogenic diets as such contribute to female familial obesity in the following generations.